Summary of household baseline survey results: Hoima District, West Central Uganda - Mubiru DN; Kristjanson, Patricia M. (2012)
Hoima District, in West Central Uganda, is predominantly agricultural. A baseline survey, supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) was undertaken in late 2010 aimed at describing the characteristics of farming systems and better understanding how they have changed over time. It also gathered information on the socio-demographic characteristics of these farming communities, basic livelihood and welfare indicators, agriculture and natural resources management practices and strategies, access and use of climate and agricultural-related information, and current risk management, mitigation and adaptation practices. Randomly selected households were the units of analysis and a face-to-face questionnaire was the primary tool that was used for data collection.